Should investors learn about the timing of equity risk? - Hasler, Michael; Khapko, Mariana; Marfè, Roberto (Journal of Financial Economics, 2019)
The term structure of equity risk has been shown to be downward sloping. We capture this feature using return dynamics driven by both a transitory and a permanent component. We study the asset allocation and portfolio performance when transitory and permanent components cannot be observed and therefore need to be estimated. Strategies that account for the observed timing of equity risk outperform those that do not, particularly so out of sample. Indeed, the mean (median) certainty equivalent return increases from about 13% (12%) to about 21% (15%) because properly modeling the timing of equity risk implies surges in portfolio returns.